Pengaruh Penyediaan Layanan Pariwisata Ramah Muslim terhadap Persepsi Wisatawan Muslim di Taman Hutan Raya Ir. Djuanda Bandung - Dadan Ramdani (Tamasya : Jurnal Pariwisata Indonesia, 2025)
Muslim-friendly tourism (halal tourism) has become a global trend in line with the increasing number of Muslim tourists, both domestic and international. Ir. H. Djuanda Grand Forest Park (Tahura Djuanda), located in Bandung, is a popular natural and educational tourism destination frequently visited by Muslim travelers, yet it has not obtained official certification as a halal tourism destination. This condition raises a question of how far the available Muslim-friendly services can influence Muslim tourists’ perceptions. This study aims to analyze the effect of Muslim-friendly tourism services on the perceptions of Muslim tourists visiting Tahura Djuanda. The research employed a quantitative descriptive and inferential method with a population of 258,975 domestic tourists who visited during January–June 2025. The sample size was determined using Slovin’s formula, resulting in 100 respondents, with 59 valid responses collected through an online questionnaire using a 5-point Likert scale. Data were analyzed using SPSS version 27, including validity, reliability, and normality tests, as well as Spearman’s Rho correlation test. The findings reveal a significant relationship between Muslim-friendly tourism services (accommodation, halal restaurants, worship facilities, halal-supporting amenities, and tour guides’ understanding) and Muslim tourists’ perceptions, which cover aspects of self, perception targets, and environmental situations. Therefore, the better the Muslim-friendly services provided, the more positive the tourists’ perceptions of Tahura Djuanda. These findings highlight the importance of implementing Muslim-friendly tourism as a strategy to improve visitor satisfaction and strengthen the competitiveness of tourism destinations.